2020
DOI: 10.1159/000505064
|View full text |Cite
|
Sign up to set email alerts
|

MiR-204-5p Inhibits Transforming Growth Factor-β1-Induced Proliferation and Extracellular Matrix Production of Airway Smooth Muscle Cells by Regulating Six1 in Asthma

Abstract: <b><i>Background:</i></b> Transforming growth factor-β1 (TGF-β1)-in­duced proliferation of airway smooth muscle cells plays critical roles in the development of airway remodeling<i>.</i> Six1 (sine oculis homeobox homolog 1) has been demonstrated to be involved in airway inflammation and remodeling in asthmatic mice. <b><i>Objectives:</i></b> The aim of this work was to investigate the potential role of miR-204-5p in the proliferation and extracellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…In ASM cells from asthmatic patients, a number of miRNAs are downregulated compared to control subjects, leading to elevated ECM expression. The expression of miR-19 is decreased in ASM cells from asthmatic patients and induces elevated expression of collagen I, fibronectin and arginine methyltransferase activity through the ERK1/MAPK signalling pathway [ 100 ]. miR-204-5p has also been shown to be down-regulated in ASM cells from asthmatic patients and promotes the expressions of fibronectin and collagen III via the Six1 gene (a TGF-β1 inducible gene) [ 101 ].…”
Section: The Ecm In Lung Remodeling and Diseasementioning
confidence: 99%
“…In ASM cells from asthmatic patients, a number of miRNAs are downregulated compared to control subjects, leading to elevated ECM expression. The expression of miR-19 is decreased in ASM cells from asthmatic patients and induces elevated expression of collagen I, fibronectin and arginine methyltransferase activity through the ERK1/MAPK signalling pathway [ 100 ]. miR-204-5p has also been shown to be down-regulated in ASM cells from asthmatic patients and promotes the expressions of fibronectin and collagen III via the Six1 gene (a TGF-β1 inducible gene) [ 101 ].…”
Section: The Ecm In Lung Remodeling and Diseasementioning
confidence: 99%
“…The stimulation of ASM cells with TGF‐β1 induces hyperproliferation and ECM production, which contribute to airway remodeling 33,34 . TGF‐β1‐stimulated ASM cells have been widely used as an in vitro model with which to study airway remodeling 35–37 . In this study, we found that AMOTL2 expression was decreased in ASM cells in response to TGF‐β1 stimulation.…”
Section: Discussionmentioning
confidence: 75%
“…Three miRNAs are interesting-miR-1, miR-155 and miR-204. These miRNAs are connected with proliferation, apoptosis, and cardiac injury [25] as well as transforming growth factor-β1 (TGF-β1) and glial cell line-derived neurotrophic factor (GDNF) regulation during glaucoma, asthma and obesity [26][27][28][29]. However, what is even more interesting is that it has been also shown that these miRNAs regulate brain-derived neurotrophic factor (BDNF) [30][31][32].…”
Section: Discussionmentioning
confidence: 99%